If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 = 7x + 6 Reorder the terms: -2 + 3x = 7x + 6 Reorder the terms: -2 + 3x = 6 + 7x Solving -2 + 3x = 6 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -2 + 3x + -7x = 6 + 7x + -7x Combine like terms: 3x + -7x = -4x -2 + -4x = 6 + 7x + -7x Combine like terms: 7x + -7x = 0 -2 + -4x = 6 + 0 -2 + -4x = 6 Add '2' to each side of the equation. -2 + 2 + -4x = 6 + 2 Combine like terms: -2 + 2 = 0 0 + -4x = 6 + 2 -4x = 6 + 2 Combine like terms: 6 + 2 = 8 -4x = 8 Divide each side by '-4'. x = -2 Simplifying x = -2
| -4+4/5x=6 | | -5=9+c-4 | | 5x-3+4x-24=3x+2+4x-9 | | -2(6+4b)=-6b | | 10y-4g-8=20 | | r/10+1.1=0.3 | | 2n+3.5=6.7 | | W^2+7=w^3+9 | | (A^-3b6-4/a^7b^3)(a^3b^4/a^-3b^-3)^2 | | 5x-3(x-5)=15 | | 2p-2=14+6p | | 6(r+7)=35+5r | | 3x=56+7(9)y | | 4t+8t=60 | | 9m+108=9m*5 | | 3k-5=2(k+1) | | 1/2(8x-5/11)-10/11(5x+3/8)=1/4(2x+5) | | X/3-8=-15 | | d/-4+3f=14 | | 5t+8t=60 | | 12=-4-11 | | -66=4+10x | | 3x+12=2x+8 | | m+12=5 | | 3z-16-z+6=0 | | 4/5+15m=v/w | | 2(1)-2=9 | | 2x+4(x-13)=2 | | -4(7+4m)-3=-8m+9 | | 7x-2=4x+4+3x-6 | | 448=3x^2+2x-8 | | (3)(5)(7)=n |